ダイ11ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 大野, 勇太; オオノ, イサダ; 里見, 穂; サトミ, ミノル; 上橋, 宏; ジョウバシ, ヒロシ; ONO, Isada; SATOMI, Minoru; JOBASHI, Hiroshi (国立極地研究所, 1971)
P(論文) This paper describes the results of meteorological observations (surface and aerological) at Syowa Station between 1 February, 1970 and 20 February, 1971. Method and instruments of observation are the same as in 1969. Observed results were regularly sent to Mawson Station. Some meteorological characters of this year are as follows 1) Temperature in the winter season was lower than the average. 2) Continuation of bad weather was experienced in April, May and July. 3) Snow accumulation was larger than that of the preceding year. 4) Strato-warming at 50mb (20km) level was one week later than the preceding year. The observations of total amount of ozone were carried out on every suitable day through the year except the polar night intervals. A specialy designed long-term meteorograph was installed at Mizuho Camp (70°42.1'S, 44°17.5'E) on 21 July, 1970. Errata | http://id.nii.ac.jp/1291/00007635/ departmental bulletin paper